Effect of Nano-Zirconium Oxide and Other Applications on Cowpea Seedlings Growth Under T Salt Stress - Habib, Amal Abdul S.; Yousif, Alyaa Muhsin (Iraqi Journal of Science, 2018)
This study was carried out in the botanical garden / department of biology /college of science in Mustansiriyah University, Baghdad. During spring 2017 under controlled environmental conditions in greenhouse to study the role of Nano ZrO2 activity in decrease negative effect of salinity under two levels from NaCl . The treatments included (Salinity levels : natural soil , 3000 ppm and 6000 ppm NaCl) and ( Applications : control , 100 , 300 Zirconium oxide , 5 ppm of liquorice root extract and 10 ppm liquorice root extract and 300 ppm GA3) , The collected data were analyzed statistically using factorial completely randomized design. The results appeared that 300 ppm nano zirconium gave the highest values in all morphological traits (except leaves number) than other treatments. In addition to the highest values in fresh weight, dry weight, Chlorophyll a, Chlorophyll b and carbohydrate contain. Also 300 ppm nano zrconium oxide reduced the effect of salinity stress (3000 and 6000 ppm NaCl) by giving the highest values in morphological traits and in chemical contains (chlorophyll and carbohydrate) in Cowpea seedling growth.